Trametes versicolor bioactive compounds stimulate Aspergillus flavus antioxidant system and inhibit aflatoxin synthesis. (3rd July 2016) - Scarpari, M.; Parroni, A.; Zaccaria, M.; Fattorini, L.; Bello, C.; Fabbri, A. A.; Bianchi, G.; Scala, V.; Zjalic, S.; Fanelli, C.
Abstract : Aflatoxins are bioactive compounds, which are toxic and carcinogenic for humans and animals, and are produced mainly by Aspergillus flavus and A. parasiticus . We studied the effect of some bioactive compounds produced into the culture filtrates of the basidiomycete Trametes versicolor on A. flavus growth and aflatoxin synthesis. Some aspects of the mechanism of action of different filtrate fractions were investigated.The results showed that these compounds stimulate the antioxidant system of the Aspergillus mycelia by the induction of a transient and modulated oxidative burst (peroxides and superoxide anions formation) perceived by Af yap 1 transcription factor. T. versicolor culture filtrate fractions, significantly inhibited aflatoxin biosynthesis (A: 75% and B: 55%) apparently by stimulating endogenous antioxidant system. In conclusion, bioactive compounds present in the T. versicolor filtrates probably act by modulating the fungal antioxidant system, eventually leading to aflatoxin inhibition. T. versicolor could represent a novel promising tool to control aflatoxins in foods and feeds.